Autorytarne decyzje dyskrecjonalne w procesie nacjonalizacji w Polsce - Kocowski, Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Nationalisation in Poland took place for and without compensation. Decisions concerning the nationalization of German companies, as declaratory decisions confirming only their adoption by law. The remaining enterprises were taken over on the basis of constitutional decisions. These were discretionary decisions to which, due to the effects caused, it was possible to successfully include the term authoritarian.
Keywords: nacjonalizacja; decyzje administracyjne; decyzje dyskrecjonalne